ISLAMIC EDUCATION ENTREPRENEURSHIP IN THE DIGITAL ERA: OPPORTUNITIES, CHALLENGES, AND INNOVATIONS - Khasanah, Arini; Widiastuti, Eka; Noviarita, Heni (FAJAR Jurnal Pendidikan Islam, 2025)
Educational entrepreneurship in the digital era has become a crucial strategy for addressing dynamic global changes. In the context of Islam, educational entrepreneurship aims not only to integrate technology into learning but also to uphold the values of justice, sustainability, and benefit for the community. This article seeks to analyze opportunities, challenges, and innovations in educational entrepreneurship, particularly from an Islamic perspective, in the digital age. Using a qualitative approach and literature study, the article explores solutions such as the development of entrepreneurship curricula grounded in Islamic values, digital competency training for educators, and strengthening entrepreneurial ecosystems through collaboration among Islamic educational institutions, government, and the private sector. This approach aims to produce a generation that is not only digitally innovative but also firmly rooted in Islamic principles to face future global challenges.